The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1136/jclinpath-2014-202524
|View full text |Cite
|
Sign up to set email alerts
|

Validation of whole slide imaging in the primary diagnosis of gynaecological pathology in a University Hospital

Abstract: AimsExperience in the use of whole slide imaging (WSI) for primary diagnosis in pathology is very limited. We aimed to determine the accuracy of interpretation of WSI compared with conventional light microscopy (CLM) in the diagnosis of routine gynaecological biopsies.MethodsAll gynaecological specimens (n=452) received over a 2-month period at the Department of Pathology of the Hospital Clinic of Barcelona were analysed blindly by two gynaecological pathologists, one using CLM and the other WSI. All slides we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 38 publications
3
56
0
Order By: Relevance
“…The first thing we could do is ensure pathologists are aware that dysplasia is a potential pitfall. Ordi et al 34 describe an increase in glass-digital concordance for cervical dysplasia as their study progressed, suggesting that there is a significant learning curve effect for digital dysplasia diagnosis. This is an area of diagnosis that may need a longer settling-in period before pathologists can confidently and safely sign out digital cases.…”
Section: Dysplasiamentioning
confidence: 99%
“…The first thing we could do is ensure pathologists are aware that dysplasia is a potential pitfall. Ordi et al 34 describe an increase in glass-digital concordance for cervical dysplasia as their study progressed, suggesting that there is a significant learning curve effect for digital dysplasia diagnosis. This is an area of diagnosis that may need a longer settling-in period before pathologists can confidently and safely sign out digital cases.…”
Section: Dysplasiamentioning
confidence: 99%
“…[1234567] One of the objectives of viewing scanned whole slides from histological or cytological specimen is remote exchange of knowledge and expertise of professionals to increase diagnostic accuracy. [12689] As a result of the increased implementation of WSI in research applications and clinical practice, guidelines for validation of WSI for use in primary diagnostics of histological specimens were recently proposed by the College of American Pathologists (CAP).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown that although diagnosis with WSI is initially more time-consuming, this time quickly decreases as pathologists become familiar with the use of the WSI viewer [30,31,32,33,34,35]. Thus, there is a learning curve in the use of WSI and the time required for making a diagnosis, and a recent study conducted at our institution confirmed that the diagnostic performance improved with practice [36]. Another limitation of WSI is the relatively high costs of the equipment.…”
Section: Advantages and Challenges Of Wsi For Routine Diagnosismentioning
confidence: 98%
“…Major discrepancies were found in only 2% of the cases, and none was related to poor image quality. Most discrepancies in this study were observed in biopsies of premalignant lesions of the uterine cervix, an area which has shown high inter- and intraobserver variability rates using CLM [36]. The magnification used in the study was ×200, and higher magnification did not seem to be required.…”
Section: Gynecological Pathologymentioning
confidence: 99%